2007
DOI: 10.4296/cwrj3203163
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Wetland Policy in Atlantic Canada

Abstract: Atlantic Canada has experienced considerable wetland loss over the past 300 years. Federal and provincial governments have responded with wetland conservation policies, regulations and other legislative tools. This paper reviews current wetland conservation policies in Atlantic Canada and explores the feasibility of a coordinated federal-provincial approach to wetland compensation in the region. The analysis indicates that although policies differ somewhat in goals and application, there is strong consensus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Many factors can affect chemical recovery of aquatic ecosystems from acidification, including climate, geochemical factors influencing storage or release of acidic compounds from forest soils as well as wetlands (Ferguson and Jeffries 2015), the latter representing a significant proportions of the land surface area in Atlantic Canada (Austen and Hanson 2007). Moreover, previous studies have suggested that, by affecting landscape properties, including vegetation and soils, increased temperature and precipitation may lead to increases in lake dissolved organic carbon (DOC), notably at high latitudes (Worrall et al 2004;Clair et al 2011;Warner et al 2020;Imtiazy et al 2020;Houle et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can affect chemical recovery of aquatic ecosystems from acidification, including climate, geochemical factors influencing storage or release of acidic compounds from forest soils as well as wetlands (Ferguson and Jeffries 2015), the latter representing a significant proportions of the land surface area in Atlantic Canada (Austen and Hanson 2007). Moreover, previous studies have suggested that, by affecting landscape properties, including vegetation and soils, increased temperature and precipitation may lead to increases in lake dissolved organic carbon (DOC), notably at high latitudes (Worrall et al 2004;Clair et al 2011;Warner et al 2020;Imtiazy et al 2020;Houle et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies cite wetland loss rates for the developed areas of Canada (e.g. Bedford, ; Warner and Asada, ; Austen and Hanson, ). Our power‐law analysis found a much lower wetland area loss within the Beaverhill watershed, a phenomenon that could be attributed to the large part of the Beaverhill watershed that is designated as parks or protected areas.…”
Section: Discussionmentioning
confidence: 97%
“…While there has been extensive work dedicated to establishing the current extent of wetlands across the island [44,45], there exists very little information as it regards to past and future trends of wetland loss and change. Rough estimates state that around 80-98% of wetlands in and around Canadian cities and two-thirds of coastal marsh in Atlantic Canada have been lost since the time of settlement [46,47]. However, the specifics of wetland loss and change in Newfoundland are not yet known.…”
Section: Study Areamentioning
confidence: 99%